Seismic performance analysis of multi-span masonry infilled RC frame based on analytical strut model. Issue 1 (September 2020) - Maidiawati, M; Tanjung, J; Nugroho, F; Hayati, Y
Abstract: According to previous studies, it was accepted that masonry infills have a contribution to lateral strength, stiffness, and ductility of reinforced concrete (RC) frames structures. In the past studies, an analytical method of diagonal strut model has developed for evaluating the seismic performance of masonry infill. In this model, the masonry infills were presented by compression struts as distributed forces at the frame-infill interfaces in which the frame-infill contact lengths were evaluated by static equilibrium related to compression balance and lateral displacement compatibility. The lateral strength of infill was determined based on frame-infill contact length. In the current study, an experimental study of quasi-static cyclic lateral loading tests was conducted to evaluate the seismic performance of two-bay brick masonry infilled RC frames. This paper discusses the results of seismic performance brick infills based on experimental and analysis results of the multi-span masonry RC frame applying the diagonal strut model. According to the analytical model, antisymmetric strut was acted at the top and bottom of the middle column of the multi-span infilled frame from each infill. As a result, good agreements of lateral strength of structures were obtained between the experimental and analytical values.